Mammalian Golgi apparatus UDP-N-acetylglucosamine transporter: Molecular cloning by phenotypic correction of a yeast mutant - Guillen, Eduardo (The National Academy of Sciences, 1998)
Transporters in the Golgi apparatus membrane translocate nucleotide sugars from the cytosol into the Golgi lumen before these can be substrates for the glycosylation of proteins, lipids, and proteoglycans. We have cloned the mammalian Golgi membrane transporter for uridine diphosphate-N-acetylglucosamine by phenotypic correction with cDNA from MDCK cells of a recently characterized Kluyveromyces lactis mutant deficient in Golgi transport of the above nucleotide sugar. Phenotypically corrected transformants were separated from mutants in a fluorescent-activated cell sorter after labeling of K. lactis cells with fluorescein isothiocyanate (FITC) conjugated to Griffonia simplicifolia II lectin, which binds terminal N-acetylglucosamine. A 2-kb DNA fragment was found to restore the wild-type cell lectin binding phenotype, which reverted to the mutant one upon loss of the plasmid. The DNA fragment contained an ORF encoding a hydrophobic, multitransmembrane spanning protein of 326 aa that had only 22% amino acid sequence identity with the corresponding transporter from K. lactis but showed 53% amino acid sequence identity to the mammalian UDP-galactose transporters and 40% to the CMP-sialic acid transporter. Golgi vesicles from the transformant regained their ability to transport UDP-GlcNAc in an assay in vitro. The above results demonstrate that the mammalian Golgi UDP-GlcNAc transporter gene has all of the necessary information for the protein to be expressed and targeted functionally to the Golgi apparatus of yeast and that two proteins with very different amino acid sequences may transport the same solute within the same Golgi membrane.